INTRINSIC ANALYSIS OF THE SHORT STORIES BY EDGAR ALLAN POE - Wuwuh Yunhadi (LINGUA : Jurnal Bahasa, Sastra, dan Pengajarannya, 2014)
This study used qualitative design. The subject of the analysis is the thematic aspect of Edgar Allan Poe's short stories. The main characteristic of Poe's short stories is the existence of what is so called a single emotional effect: all incidents in the story, the words and details that create the incident, must point toward this single, effect. Poe is known as the possessor of one most original imagination (Cline, 1969). Eight Poe's short stories were selected as subjects. The primary source of data is the eight short stories by Edgar Allan Poe. The secondary source of data is criticism, Poe's biographical note, ideas, theories, basic principles, opinions. The subject matters of Edgar Allan Poe's selected short stories. The themes of the short stories are (1) madness brings harm, (2) drinking too much alcohol cause catastrophic, (3) revenge exist even in a close friendship, (4) people are helpless when confronted to God's power, (5) love gets rid of the memory, (6) true friend will always be at our side,  (7) God shows power through miracle and disaster; and (8) mental disorder can be hereditary features.